Association between insulin resistance, metabolic syndrome and its components and lung cancer: a systematic review and meta-analysis - Jingxuan Liu; Rui Wang; Song Tan; Xiaohu Zhao; Aihua Hou (Diabetology & Metabolic Syndrome, 2024)
Abstract Background A growing body of evidence points to the association between insulin resistance (IR), metabolic syndrome (MetS) and its components and lung cancer incidence, but remains controversial and unknown. Methods A systematic search was conducted through PubMed, Embase, Cochrane Library, the China National Knowledge Infrastructure (CNKI) and Wanfang databases for the corresponding studies. Each study reported the risk estimate and 95% confidence intervals (CI) for lung cancer, and a fixed effects model or random effects model was used for outcome. Results We included 31 publications involving 6,589,383 people with 62,246 cases of lung cancer. Diabetes mellitus (DM) (RR = 1.11, 95% CI  1.06–1.16, P = 0.000) and IR (RR = 2.35, 95% CI  1.55–3.58, P = 0.000) showed a positive association with lung cancer risk. BMI (RR = 0.66, 95% CI  0.54–0.81, P = 0.000) and HDL-C (RR = 0.88, 95% CI  0.79–0.97, P = 0.010) were negatively correlated with lung cancer. MetS(RR = 0.99, 95% CI  0.90–1.09, P = 0.801), TC (RR = 0.93, 95% CI  0.81–1.06, P = 0.274), TG (RR = 0.99, 95% CI  0.88–1.12,P = 0.884), LDL-C (RR = 1.01, 95% CI  0.87–1.16, P = 0.928), hypertension (RR = 1.01, 95% CI  0.88–1.15, P = 0.928), FBG (RR = 1.02, 95% CI  0.92–1.13, P = 0.677) and obesity (RR = 1.11, 95% CI  0.92–1.35, P = 0.280) were not associated with lung cancer. Conclusion Our study showed that the risk of lung cancer is correlated with DM, IR, BMI, and HDL-C. Timely control of these metabolic disorders may have a positive effect on preventing lung cancer. Trial registration Our study has been registered in the Prospective Register of Systematic Reviews (PROSPERO), ID: CRD42023390710.